Gender and Human Security: A Theoretical Discourse on Feminist Perspectives - Yakubu , Funom Rapha; Olabisi , Aina (Corpus Intellectual, 2025)
A feminist perspective emphasizes the consequences of masked disparities muddled under the umbrella of “human” in relation to an extended human security paradigm. The politics of numerous overlapping identities are, therefore, a focus of a critical feminist approach to the discourse of human security. Under the lens of feminism, security discourse may become more self-aware of its own normative presumptions. This paper reviews diverse feminist perspectives over the years on the subject of gender as it intersects with race, class, nationality and security. It discovers that the tension between universalism and cultural relativism on the subject is resolved by tying different individual experiences in a specific area to larger regional and global structures and processes. Gender is connected with other identities, such as race, class and nationality. Hence, the degree of universalizing tendencies and gender silences within security discourses may be seen by taking a look at several feminist and security studies perspectives. The conceptual and political correlation between gender and security is frequently disregarded. The contradiction of human security as both a political mission of emancipation and an analytical framework may thus be clarified through a focus on identity politics. Hence, a case is presented through a meta-analysis of existing literature for gender interpretations in human security that is more flexible and dependent on the situation. In this sense, it is suggested that alternative feminist perspectives, such as those anchored in the African and black context, can make it easier to communicate across and among groups of people who hold seemingly discordant viewpoints.